Konsep Pendidik dalam Paradigma Profetik untuk Menghadapi Era Society 5.0 - Fatkhatul Mar'ah; Moh. Roqib (Jurnal Penelitian Agama, 2021)
Pious people who have skill on technology are needed to be an educators in the face of society 5.0. This era requires educators to be innovative both in presenting the learning material and in interacting with students in the class. This paper aims to analyze the concept of teachers from the prophetic paradigm to face the era of Society 5.0. The use of technology will occur universally in this era. It means humans life are closer related to technology, including in education field. This research used descriptive qualitative methods with library research as an approach. Data is obtained by collecting some literature that has links to needs of educator characteristics from prophetic paradigm in society 5.0 either from books, journals, and magazines. This paper founded educators in prophetic paradigm is who imitate prophet characteristics and behavior, so that increase their skill in teaching. Creative, innovative and smart are prophet characteristic should be there in teacher to face the era of society 5.0. Some innovations that can be applied by teachers include: religious literacy, the use of HOTS (High, Order, thinking, skills) questions in everyday life, prophetic communication, creating educational content, increasing teachers competence, education for all groups and using the internet for positive things.